Human mRNA Response to Exercise and Temperature - Slivka, D. R.; Dumke, C. L.; Tucker, T. J.; Cuddy, J. S.; Ruby, B. (International Journal of Sports Medicine, 2012)
The purpose of this research was to determine the mRNA response to exercise in different environmental temperatures. 9 recreationally active males (27±1 years, 77.4±2.7 kg, 13.5±1.5% fat, 4.49±0.15 L · min − 1 VO2 max) completed 3 trials consisting of 1 h cycling exercise at 60% Wmax followed by a 3 h recovery in the cold (7°C), room temperature (20°C), and hot (33°C) environments. Muscle biopsies were obtained pre, post, and 3 h post exercise for the analysis of glycogen and mRNA. Expired gases were collected to calculate substrate use. PGC-1α increased to a greater degree in the cold trial than in the room temperature trial (p=0.036) and the hot trial (p=0.006). PGC1-α mRNA was also higher after the room temperature trial than the hot trial (p=0.050). UCP3 and MFN2 mRNA increased with exercise (p<0.05), but were unaffected by temperature. COX was unaffected by exercise or temperature. Muscle glycogen decreased with exercise (p<0.05), but was no different among trials. Whole body VO2 was lower during exercise in the cold than exercise in the heat. However, VO2 was higher during recovery in the cold trial than in the room temperature and hot trials (p<0.05). This study presents evidence of PGC-1α temperature sensitivity in human skeletal muscle.
Keywords: hot; cold; PGC1; MFN2; COX; UCP3